Comparative Analysis of the Effectiveness of Physics Learning Outcomes Against Online and Offline Learning at Public High School 1 Tikep - Jahiruddin Jahiruddin; Yasir Salih (Research Collaboration Community (RCC), 2023)
The Covid-19 pandemic has had a significant impact on education in Indonesia. From 2020 to 2021, the government requires that the learning process be carried out online. However, in early 2022 the government allowed schools in several areas to carry out offline (face-to-face) learning by implementing strict health protocols. Therefore, this study's purpose was to compare the effectiveness of physics learning outcomes against online and offline learning at SMA Negeri 1 Tikep. This study uses a quantitative method approach in analyzing physics learning outcomes. The data used in this study were 116 sample data obtained from a questionnaire given to class X IPA students at SMAN 1 Tikep. Based on the study's results, it was found that as many as 98% of students were happy with offline learning, while only 36% were happy with online learning. Offline physics learning is effective for student learning outcomes, while online learning is less effective. Students learning motivation in taking physics lessons offline has increased by 100%. When compared to student learning motivation in participating in online physics learning, it is only 17.24%. Based on the study results, it can be concluded that online physics learning at SMAN 1 Tikep cannot run effectively. The results of this study are expected to be used as material for evaluating the government in the distribution of education in Indonesia, especially in the procurement of Information and Communication Technology (ICT) facilities.